2018
DOI: 10.1122/1.5046893
|View full text |Cite
|
Sign up to set email alerts
|

Wall slip mechanisms in direct and inverse emulsions

Abstract: We carry out a series of experiments with the aim of completing our knowledge of wall slip characteristics, through a deductive approach based on macroscopic behavior observations. More precisely, we use model materials (direct and inverse emulsions) and determine the variations of wall slip properties depending on the material parameters (droplet size, concentration) and boundary conditions of the flow (free surface or flow between two solid surfaces, normal force, flow beyond yielding, and coated or rough su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
2
13
1
Order By: Relevance
“…Note that all measurements are performed for wall stresses above the yield stresses σ Y , while previous measurements by Seth et al [17] suggested a transition in slip regimes at σ w ≈ σ Y . In this stress range, we also detect no measurable wall yield stress, contrary to measurements from the recent literature [10,17,21].…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Note that all measurements are performed for wall stresses above the yield stresses σ Y , while previous measurements by Seth et al [17] suggested a transition in slip regimes at σ w ≈ σ Y . In this stress range, we also detect no measurable wall yield stress, contrary to measurements from the recent literature [10,17,21].…”
Section: Resultscontrasting
confidence: 99%
“…To conclude, we have demonstrated that the slip friction of jammed microgel suspensions exhibits a robust transition from a non-linear regime to a linear one at large wall stresses and slip velocities. We thereby reconcile seemingly contradictory measurements from the literature regarding slip laws of yield stress fluids above the yield stress [5,8,17,21].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Meeker et al (2004b) and Piau (2007) tried to theoretically describe the slip origin in soft particle pastes/microgels from an elastohydrodynamic perspective. Rheometric tests with slippery plates in the cone-plate/plate-plate geometries have been conducted to quantify the slip behaviours of yield-stress fluids ranging from Carbopol gels to emulsions (Meeker, Bonnecaze & Cloitre 2004a;Meeker et al 2004b;Poumaere et al 2014;Zhang et al 2018). Moreover, very recently, in a series of experiments using optical coherence tomography (known as OCT) and particle tracking velocimetry (known as PTV), Daneshi et al (2019) characterized the slip behaviour of Carbopol gel (a model 'simple' yield-stress fluid) inside a capillary tube.…”
Section: General Slip Law For Yield-stress Fluidsmentioning
confidence: 99%
“…2014; Zhang et al. 2018). Moreover, very recently, in a series of experiments using optical coherence tomography (known as OCT) and particle tracking velocimetry (known as PTV), Daneshi et al.…”
Section: Introductionmentioning
confidence: 99%